Ketamine Use in Operation Enduring Freedom. Issue 7 (1st July 2021) - Leslie, Eric; Pittman, Eric; Drew, Brendon; Walrath, Benjamin
ABSTRACT: Introduction: Ketamine is a dissociative anesthetic increasingly used in the prehospital and battlefield environment. As an analgesic, it has been shown to have comparable effects to opioids. In 2012, the Defense Health Board advised the Joint Trauma System to update the Tactical Combat Casualty Care Guidelines to include ketamine as an acceptable first line agent for pain control on the battlefield. The goal of this study was to investigate trends in the use of ketamine during Operation Enduring Freedom (OEF) and Operation Freedom's Sentinel (OFS) during the years 2011-2016. Materials and Methods: A retrospective review of Department of Defense Trauma Registry (DoDTR) data was performed for all patients receiving ketamine during OEF/OFS in 2011-2016. Prevalence of ketamine use, absolute use, mechanism of injury, demographics, injury severity score, provider type, and co-administration rates of various medications and blood products were evaluated. Results: Total number of administrations during the study period was 866. Ketamine administration during OEF/OFS increased during the years 2011-2013 (28 patient administrations in 2011, 264 administrations in 2012, and 389 administrations in 2013). A decline in absolute use was noted from 2014 to 2016 (98 administrations in 2014, 41 administrations in 2015, and 46 administrations in 2016). The frequency of battlefield ketamine use increased from 0.4% to 11.3% for combat injuries sustained in OEF/OFS from 2011 to 2016. Explosives (51%) and penetrating trauma (39%) were the most common pattern of injury in which ketamine was administered. Ketamine was co-administered with fentanyl (34.4%), morphine (26.2%), midazolam (23.1%), tranexamic acid (12.3%), plasma (10.3%), and packed red blood cells (18.5%). Conclusions: This study demonstrates increasing use of ketamine by the U.S. Military on the battlefield and effectiveness of clinical practice guidelines in influencing practice patterns.